Mosquito Nets Use in South Central Timor District is Significantly Liked to Incidence of Malaria - Nisa Fauziah; Reyhan Luthfierza Fauzan; Naufal Fakhri Nugraha; Lia Faridah; Jontari Hutagalung (Faculty of Medicine, Universitas Padjadjaran, 2022)
Ninety percent of malaria cases in Indonesia come from Papua, West Papua, and East Nusa Tenggara provinces. The country has declared a target of malaria elimination by 2030. Malaria elimination efforts have been performed through case finding, treatment, surveillance, and risk factor prevention and control. Personal protection is crucial in preventing and reducing the risk for malaria infection. This study aimed to assess the significance of personal protection against mosquitoes in eastern Indonesia. This was a cross-sectional study using the secondary data from a previous study of malaria in eastern Indonesia in 2013–2014. Data were collected using a questionnaires and direct observation and analyzed using the chi-square with α 0.05 and 95% CI. A total of 551 data were collected (180 positive vs 371 negative). The use of mosquito nets at night (p-value: 0.038; OR: 3.127) has a significant relationship with the incidence of malaria while the use of ventilation screen (p-value: 0.191; OR: 0.839), vector shelter (p-value: 0.493; OR: 0.852), and mosquito repellent (p-value: 0.564; OR: 1.585) did not have significant relationships to the incidence of malaria. Mass distribution of mosquito nets by the local governments can constitute one of the efforts to prevent and control malaria in South Central Timor District.